A matched case–control study of toxoplasmosis after allogeneic haematopoietic stem cell transplantation: still a devastating complication. (July 2016) - Conrad, A.; Le Maréchal, M.; Dupont, D.; Ducastelle-Leprêtre, S.; Balsat, M.; Labussière-Wallet, H.; Barraco, F.; Nicolini, F.-E.; Thomas, X.; Gilis, L.; Chidiac, C.; Ferry, T.; et al.
Abstract: Toxoplasmosis (TXP) is a life-threatening complication of allogeneic haematopoietic stem cell transplantation (AHSCT). Little is known about the risk factors and there is no consensus on prophylactic measures. To investigate the risk factors, we conducted a single-centre, retrospective matched case–control study among adults who underwent AHSCT from January 2006 to March 2015 in our hospital. TXP cases were identified from the prospectively maintained hospital's database. The 1:2 control population consisted of the two patients who received an AHSCT immediately before and after each case with similar donor relationship (related, unrelated) but who did not develop TXP. Risk factors were identified by conditional logistic regression. Clinical features and outcome of TXP were examined. Twenty-three (3.9%) cases of TXP (20 diseases, three infections) were identified among 588 AHSCT recipients. Twenty (87%) cases had a positive pre-transplant Toxoplasma gondii serology. In comparison with 46 matched control patients, risk factors were the absence of effective anti- Toxoplasma prophylaxis (odds ratio (OR) 11.95; 95% CI 3.04–46.88; p <0.001), high-grade (III–IV) acute graft-versus-host-disease (OR 3.1; 95% CI 1.04–9.23; p 0.042) and receipt of the tumour necrosis factor-α blocker etanercept (OR 12.02; 95% CI 1.33–108.6; p 0.027). Mortality attributable to TXP was 43.5% ( n  = 10). Non-relapse mortality rates during the study period of cases and controls were 69.6% ( n  = 16) and 17.4% ( n  = 8), respectively. Lung involvement was the dominant clinical feature ( n  = 14). Two cases were associated with graft failure, one preceded by haemophagocytic syndrome. Given TXP-related morbidity and attributable mortality, anti- Toxoplasma prophylaxis is essential for optimized management of seropositive AHSCT recipients.